جهود ابن عاشور في الإصلاح التربوي من خلال "التحرير والتنوير" سورة يوسف أنموذجا - محمد، عزالدين علي عبد المولى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study focuses on the efforts of Ibn Ashour in the educational reform through his book “Interpretation of Verification and Enlightenment”. This study highlights some of these reform issues by focusing on Surah Yusuf as its verses contain many of the educational subjects that mankind needs in solving the problems that have affected society and because the Surah represents a fundamental reform framework. The inductive method was used in this study to extrapolate the educational issues raised by Ibn Ashour in his interpretation of Surah Yusuf. One of the most important findings of this study is that the interpretation of verification and enlightenment is full of educational issues, especially the issues that have been clarified by Surah Yusuf. The first issue is the strong relationship between Father Jacob (Yaqub) and his son Joseph (Yusuf) peace be upon them and how to benefit from it in strengthening the family relationship, the second issue is envy among brothers which infects many families and how Jacob solved that problem.